Biodiversity assessment of the vegetation in the Phuninh water-reservoir basin, Quangnam province for the rational use - Thuy, Tran Van; Phuong Anh, Dinh Thi; Dao, Nguyen Thi; Can, Vu Van (Academia Journal of Biology, 2014)
Based on the analysis of the field survey biodiversity data in 2005, the flora of the Phuninh water-reservoir basin (Quangnam province) is inventoried with 290 species of 4 phylla (Lycopodiophyta, Polypodiophyta, Pinophyta and Magnoliophyta). Among them, 8 threatened species are listed in the Red Data Book of Vietnam (plants), 1996 and many species have high economic and scientific values. These species distribute in 5 communities of 2 tropical evergreen forest formations. The thick evergreen tropical forest in low land and the one in low mountain are most important in the basin. They are very high biodiversity communities as well as highly capable to minimize the soil erosion, to keep the long working time for the reservoir. Beside that, the paper proposes 4 cures for the rational utilization.